Pengaruh Penilaian Kinerja, Kompetensi, Pelatihan Kerja Dan Kompensasi Terhadap Kinerja Karyawan Dengan Motivasi Sebagai Variabel Intervening Pada PT. Perkebunan Nusantara IV Regional 1 - Zulfan, Helmi; Noer, Zulheri; Simanullang, Endang Sari (JURNAL AGRICA, 2025)
PTPN IV Regional 1 Medan experienced several problems related to employee performance, meanwhile there is an imbalance in the number of employees with the existing workload, as well as a suboptimal work system. The aim of this study was to analyze the effect of performance assessment, competence, job training and compensation on employee performance with motivation as an intervening variable. This study was conducted at the PT. Perkebunan Nusantara IV Regionall Medan with a sample of 252 person with stratified random sampling and the analysis technique in this study using the Plartial Lealst Squalre (PLS) approach. The results showed that the variables of performance, competence, job training, compensation, motivation have a direct effect on employee performance. The variables of performance, competence have an indirect effect on employee performance through the motivation variable while the variables of job training and compensation do not have an indirect effect.